DOCUMENTATION OF FINANCED COSTS OF FINISHED PRODUCTION AT AN INDUSTRIAL ENTERPRISE - PRYKHODKO, MARYNA; BELOZERTSEV, VASYL; KHARAKOZ, LILYA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Understanding the importance of costs is important for effective enterprise management. Cost analysis helps to determine the level of the company, calculate the optimal cost, rationally set prices, plan the level of profit and profitability. Carrying out economic and production activities, the company consumes raw materials, fuel, energy, pays wages to employees who are charged for social and pension insurance, and bears other costs. That is, production costs refer to the costs incurred by the company in the manufacture of products or provision of works and services. Production costs are directly related to the income of the enterprise, as it is reimbursed from the proceeds from the sale of products (works, services), which ensures the continuity of the production process. The costs of the enterprise in accounting are reflected in a single monetary expression, and ultimately constitute the cost. Accounting of finished products is carried out on the basis of proper processing and execution of the relevant primary documents. Technologically, accounting as a process begins with the detection, measurement and registration of facts, actions and events in order to obtain information about business transactions. Thus, continuous monitoring of all business transactions at the enterprise is carried out through documentation. This article reveals the essence and significance of accounting documentation for the production of finished products, as well as synthetic and analytical cost accounting on the example of an individual enterprise, namely the Limited Liability Company «Tokmatskyi kovalsko - shtampuvalnyi zavod», which are directly included in the cost of finished products. The practical value of the results of the study lies in the possibility of implementing recommendations in the activities of industrial enterprises, which will improve the quality, efficiency of processing accounting information and profitability of the enterprise.